Investigating ApoE4-Mediated Molecular Alterations in H4 Neuroglioma Cells of Alzheimer’s Disease Using OrbiSIMS and LC-MS/MS. - Lu, Li (2025)
Apolipoprotein E4 (ApoE4) is the significant risk gene for late-onset Alzheimer’s disease (AD), which is not only associated with the AD pathological features, including amyloid-β deposition, phosphorylation of Tau proteins and neuroinflammation; but also involved with metabolism, neuron growth, and synaptic plasticity. Growing clinical evidence has revealed that dysfunction of systematic molecular alterations in the brain occurs even twenty years before the onset of AD pathological features. Multi-omics such as metabolomics and proteomics have been applied widely in identifying key disease-related molecular alteration and disease-progression-related changes. Despite recent advances in the development of analytical technologies, screening the whole profile of metabolites remains challenging, due to many classes of compounds with diverse chemical properties that would need different extraction processes. In this study, we combined two omics (metabolomics and proteomics) to study the molecular alteration effected by ApoE4 in H4 neuroglioma cells. Typically, we first conducted metabolomics that uses Orbital trapping secondary ion mass spectrometry (OrbiSIMS) as a screening tool to gain a non-biased overview of metabolic alteration under ApoE4-carried neuroglioma cells. Sample preparation optimisation for H4 cells in OrbiSIMS analysis has been conducted under two conditions: freeze-dried and frozen-hydrated. The findings are subsequently followed by LC-MS/MS targeted metabolomics for further confirming specific metabolite classes. Then proteomics was also performed by using UHPLC-MS. Subsequentially, Gene ontology (GO) analysis has been applied to link the metabolomics and proteomics results. The initial OrbiSIMS approach has shown the advantages of detecting large numbers of metabolites with minimal sample preparation, small sample size and a relatively rapid analysis time, allowing 192 putatively annotated metabolites detected in our study. Overall, OrbiSIMS as screening tool then followed by LC-MS/MS is successfully developed to investigate cellular metabolomics, revealing the disruption of lipid metabolism (glycerophospholipids and sphingolipids) and amino acid metabolism. This includes alanine, aspartate, and glutamate metabolism, aminoacyl-tRNA biosynthesis, glutamine metabolism, and taurine and hypotaurine metabolism. Proteomics study further confirms the dysfunction of amino acids, tRNA aminoacylation metabolic processes, and reveals RNA splicing process affected by ApoE4. GO analysis suggests that nitrogen compounds, amino acids, tRNA aminoacylation metabolic processes play important roles in ApoE4 mediated molecular alterations in AD.